Effect of the alcohol consumption on osteocyte cell processes: a molecular imaging study. Issue 8 (15th August 2013) - Maurel, Delphine B.; Benaitreau, Delphine; Jaffré, Christelle; Toumi, Hechmi; Portier, Hugues; Uzbekov, Rustem; Pichon, Chantal; Benhamou, Claude L.; Lespessailles, Eric; Pallu, Stéphane
Abstract We have previously shown microarchitectural tissue changes with cellular modifications in osteocytes following high chronic alcohol dose. The aim of this study was to assess the dose effect of alcohol consumption on the cytoskeleton activity, the cellular lipid content and modulation of differentiation and apoptosis in osteocyte. Male Wistar rats were divided into three groups: Control (C), Alcohol 25% v/v (A25) or Alcohol 35% v/v (A35) for 17 weeks. Bone mineral density (BMD) was assessed by DXA, osteocyte empty lacunae, lacunae surface, bone marrow fat with bright field microscopy. Osteocyte lipid content was analysed with transmission electron microscopy (TEM) and epifluorescence microscopy. Osteocyte apoptosis was analysed with immunolabelling and TEM. Osteocyte differentiation and cytoskeleton activity were analysed with immunolabelling and real time quantitative PCR. At the end of the protocol, BMD was lower in A25 and A35 compared with C, while the bone marrow lipid content was increased in these groups. More empty osteocyte lacunae and osteocyte containing lipid droplets in A35 were found compared with C and A25. Cleaved caspase‐3 staining and chromatin condensation were increased in A25 and A35 versus C. Cleaved caspase‐3 was increased in A35 versus A25. CD44 and phosphopaxillin stainings were higher in A35 compared with C and A25. Paxillin mRNA expression was higher in A35 versus A25 and C and sclerostin mRNA expression was higher in A35 versus C. We only observed a dose effect of alcohol consumption on cleaved caspase‐3 osteocyte immunostaining levels and on the number of lipid droplets in the bone marrow.